The value of wheat shorts in coarse and fine ground concentrate mixtures for fattening heifers - Smith, E.F.; Richardson, D.; Kramer, J.E. (Kansas Agricultural Experiment Station, 2011)
Twenty-four yearling Hereford heifers with a USDA Feeder Grade of about High Good were divided on the basis of prior treatment and on a random-weight basis into four groups of six heifers each. The experimental diet is listed in Table 53. Two lots of six each received wheat shorts to increase the protein content of the corn based ration to 10.5 percent protein, two lots received soybean oil meal in their mixture to raise the protein content to the same level. One lot fed wheat shorts and one lot fed soybean meal received their concentrate mixture fine ground: in the other wheat shorts and soybean meal lots, the mixture was fed in a medium-coarse ground form. The cattle were fed twice daily for about 60 days and then self-fed the latter part of the trial. No roughage was fed about the last 30 days of the trial.
Keywords: Beef; Wheat shorts; Soybean meal; Concentrate